Cellular barcoding: A technical appraisal - Naik, Shalin H.; Schumacher, Ton N.; Perié, Leïla (Experimental hematology, 2014)
Cellular barcoding involves the tagging of individual cells of interest with unique genetic heritable identifiers or barcodes and is emerging as a powerful tool to address individual cell fates on a large scale. However, as with many new technologies, diverse technical and analytical challenges have emerged. Here, we review those challenges and highlight both the power and limitations of cellular barcoding. We then illustrate the contribution of cellular barcoding to the understanding of hematopoiesis and outline the future potential of this technology.